Neurofibromatosis type I and malignancy: a monoinstitutional report - Scalzone, Maria; Coccia, Paola Coccia; Liotti, Lucia; Lazzareschi, Ilaria; Ruggiero, Antonio; Riccardi, Riccardo (European Journal of Oncology and Environmental Health, 2008)
Neurofibromatosis type (NF1) I is one of the most common autosomal dominant disorders. The phenotype is extremely heterogeneous because of the expression of various clinical features and a large variety of mutations that have been identified up to now. Affected individuals are more prone to develop malignancy. The optic pathway glioma is one of the most common complications and its behaviour is completely unpredictable: treatment is performed only when clinical or radiological signs of progression are detected. In our NF1 series, we describe the clinical features of 18 children affected by the tumour, evaluating, for each patient, the age, the criteria used for NF1 diagnosis, the tumour type, the age at presentation, the symptomatology at presentation, and monitoring the clinical evolution over time. Most patients were found to be affected by optical gliomas in addition to other clinical manifestations involving the skin, the visual system, the central and peripheral nervous systems, the skeleton, and the cardiovascular, gastroenteric and endocrine systems. About 40% of them did not need any therapy and the majority presented stability of the disease. Athorough understanding is crucial for proper medical management and patient education.